Organic photovoltaic module development with inverted device structure. Issue 1737 (29th May 2015) - Mori, Shigehiko; Oh-oka, Haruhi; Nakao, Hideyuki; Gotanda, Takeshi; Nakano, Yoshihiko; Jung, Hyangmi; Iida, Atsuko; Hayase, Rumiko; Shida, Naomi; Saito, Mitsunaga; Todori, Kenji; Asakura, Taro; et al.
ABSTRACT: The power conversion efficiency (PCE) of organic photovoltaic (OPV) modules with 9.5% (25 cm 2 ) and 8.7% (802 cm 2 ) have been demonstrated. This PCE of the module exceeded our previous world records of 8.5% (25 cm 2 ) and 6.8% (396 cm 2 ) that were listed in the latest Solar Cell Efficiency Tables ver.43 [1]. Both module design and coating/patterning technique were consistently studied for module development. In order to achieve highly efficient modules, we increased the ratio of photo-active area to designated illumination area to 94% without any scribing process and placed insulating layers in order to decrease the leakage current. The meniscus coating method was used for the fabrication of both buffer and photoactive layers. This technique ensures the fabrication of uniform and nanometer order thickness layers with thickness variation less than 3%. Furthermore, the PCE of the OPV under indoor illumination was found to be higher than that of the conventional Si type solar cells. This indicates that OPVs are promising as electrical power supplies for indoor applications. Therefore, we have also developed several prototypes for electronics integrated photovoltaics (EIPV) such as electrical shelf labels and wireless sensors embedded with our OPV modules, which can be operated by indoor lights.